Anomie or imitation? The Werther effect of celebrity suicides on suicide rates in 34 OECD countries, 1960-2014 - Mark Lutter; Karlijn L. A. Roex; Daria Tisch (Max Planck Institute for the Study of Societies, 2018)
Anomie and imitation have been prominent mechanisms explaining the Werther effect, i.e., the effect of celebrity suicides on a general population's suicide rate. This study presents a new approach to empirically disentangle both mechanisms. Imitation theory suggests that celebrities act as role models, and that the Werther effect is triggered by the status of the celebrity in question. Anomie theory, on the other hand, suggests that the Werther effect is triggered by the unexpectedness of the event. To this end, we empirically compare the effects of celebrity suicides with the effects of celebrities who died unexpectedly from causes other than suicide (accidents, illnesses, alcohol abuse). Based on language and page-link data from 3,855 Wikipedia pages of 495 celebrities who committed suicide between 1960 and 2014, we measure the status a celebrity has in a particular country and calculate the potential country-specific imitation effect of their suicide. In the same manner, we measure status effects of celebrities who died unexpectedly from accidents, illnesses, or alcohol abuse to reflect anomie-related effects. We use these measures in a time-series cross-sectional dataset for 34 OECD countries to assess their effects on a country's overall annual suicide rate. Fixed-effects analyses reveal that country-specific status effects of celebrity suicides lead to significant increases in overall suicide rates, while anomie-related, unexpected celebrity deaths show no effects. The findings remain robust across a number of alternative specifications, such as controlling for further anomic factors at the macro level (divorce or unemployment rate, for instance). We conclude that the results support the imitation mechanism as an essential social explanation for the Werther effect. – – Anomie und Imitation sind zwei wichtige Mechanismen zur Erklärung des Werther-Effektes, also der Annahme, dass es einen kausalen Zusammenhang zwischen Selbstmorden berühmter Personen und der allgemeinen Selbstmordrate gibt. Die vorliegende Studie präsentiert nun einen neuen Ansatz, der versucht, beide Mechanismen empirisch voneinander zu trennen. Imitationstheorien gehen davon aus, dass Berühmtheiten als Rollenvorbilder fungieren und dass der Werther-Effekt somit durch die Statushöhe der Berühmtheiten erklärt werden kann. Anomietheorien nehmen dagegen an, dass der Werther-Effekt eher durch die unerwartete Plötzlichkeit des Ereignisses erklärt werden kann. Wir vergleichen daher empirisch den Einfluss von Selbstmorden berühmter Personen mit dem plötzlich und unerwartet durch Unfälle, Krankheiten oder Alkoholmissbrauch gestorbener Berühmtheiten. Auf Basis der Sprach- und Page-Link-Daten von 3.855 Wikipedia-Seiten der 495 Berühmtheiten, die zwischen 1960 und 2014 durch Suizid gestorben sind, erfassen wir ein Maß für den Status und Einfluss, den die Personen in einem bestimmten Land aufweisen, und schätzen darüber den potenziellen Nachahmereffekt ihres Selbstmordes. Anomie-bezogene Effekte erfassen wir, indem wir Berühmtheiten einbeziehen, die unerwartet durch Unfälle, Krankheiten oder Alkoholmissbrauch gestorben sind. Wir nutzen diese Maße, um mithilfe eines gepoolten Paneldatensatzes für 34 OECD-Länder ihre Effekte auf die allgemeine Selbstmordrate zu schätzen. Fixed-Effects-Analysen zeigen, dass das Statusmaß mit einem signifikanten Anstieg der länderspezifischen Selbstmordraten einhergeht. Zugleich zeigen sich keine Effekte der anomiebezogenen Maße zu den unerwartet durch Krankheiten, Unfälle oder Alkoholmissbrauch gestorbenen Berühmtheiten. Die Ergebnisse erweisen sich als robust über eine Reihe alternativer Spezifikationen wie beispielsweise der Konstanthaltung weiterer Anomie-Faktoren auf der Makroebene (zum Beispiel Scheidungs- oder Arbeitslosenraten). Aus diesen Ergebnissen schließen wir, dass der Werther-Effekt wesentlich durch Mechanismen der Nachahmung erklärt werden kann.
hdl:21.11116/0000-0001-547E-4
Keywords: 300; anomie; imitation; celebrity suicides; contagion; status; suicide; Werther effect; Wikipedia; Ansteckung; Suizid; Suizid berühmter Personen; Werther-Effekt